Preoperative Pressure Ulcers, Mortality, and Complications in Older Hip Fracture Surgery Patients. (2nd November 2022) - Porter, Steven B.; Pla, Raymond; Chow, Jonathan H.; Keneally, Ryan; Douglas, Rundell; Desvarieux, Tricia; Crowe, Matthew M.; Mazzeffi, Michael A.
Abstract : Introduction: The effect of a preoperative pressure ulcer (PPU) in hip fracture patients on postoperative outcomes has not been well studied. We hypothesized that the presence of a PPU would be associated with increased mortality and serious complications in hip fracture surgery patients. Methods: We conducted a cohort study of 19, 520 hip fracture patients from 2016 to 2019 with data from the National Surgical Quality Improvement Program. The study exposure was the presence of a PPU. This study's primary outcome was 30-day mortality. Secondary outcomes included deep vein thrombosis (DVT), pulmonary embolism, surgical site infection, pneumonia, and unplanned hospital readmission. Propensity score analysis and inverse probability of treatment weighting were used to control for confounding and reduce bias. Results: The presence of a PPU was independently associated with a 21% increase in odds of 30-day mortality (odds ratio (OR) = 1.2, P = 0.004). The presence of a PPU was also independently associated with increased odds of DVT (OR = 1.59, P < 0.001), pneumonia (OR = 1.39, P < 0.001), and unplanned hospital readmission (OR = 1.43, P < 0.001) and a significant increase in the mean length of hospital stay of 0.4 days ( P = 0.007). Discussion: We found that PPUs were independently associated with increased 30-day mortality, DVT, pneumonia, hospital length of stay, and unplanned hospital readmission.